2021
DOI: 10.21203/rs.3.rs-224184/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Likelihood Ratio Test For The Homogeneity of Between-Study Variance in Network Meta-Analysis

Abstract: Background: Network meta-analysis (NMA) is a statistical method used to combine results from several clinical trials and simultaneously compare multiple treatments using direct and indirect evidence. Statistical heterogeneity is a characteristic describing the variability in the intervention effects being evaluated in the different studies in network meta-analysis. One approach to dealing with statistical heterogeneity is to perform a random effects network meta-analysis that incorporates a between-study varia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…47 Hu et al proposed a likelihood ratio test for the homogenous variance assumption and found significant difference of two heterogeneity parameters between comparisons for non-active control to active treatments and comparisons for active to active treatments. 58 If the homogenous variance assumption does not hold, using the NMA model with the assumption of homogenous variance will influence the point estimates and confidence intervals of treatment effects, 58 and distort the treatment ranking probabilities. 47 Similarly, the assumption of common between-study correlation may be violated in NMA.…”
Section: Discussionmentioning
confidence: 99%
“…47 Hu et al proposed a likelihood ratio test for the homogenous variance assumption and found significant difference of two heterogeneity parameters between comparisons for non-active control to active treatments and comparisons for active to active treatments. 58 If the homogenous variance assumption does not hold, using the NMA model with the assumption of homogenous variance will influence the point estimates and confidence intervals of treatment effects, 58 and distort the treatment ranking probabilities. 47 Similarly, the assumption of common between-study correlation may be violated in NMA.…”
Section: Discussionmentioning
confidence: 99%